Village Apparatus Performance in “Jotacorubo” Village, Weru District - Tri Gono; Istatin; Sudarwati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to examine the influence of the variables of Leadership, Utilization of Information Technology, Competence, and Communication on the Performance of Village Apparatus. In this study, the author uses a quantitative descriptive method to determine the magnitude and significance of the influence between variables. The research was conducted in the village of